Iron phosphide/N, P-doped carbon nanosheets as highly efficient electrocatalysts for oxygen reduction reaction over the whole pH range - Hu, K.; Xiao, Z.; Cheng, Yi; Yan, D.; Chen, R.; Huo, J.; Wang, S. (Pergamon, 2017)
© 2017 Elsevier Ltd Developing electrocatalysts with both high activity and low cost for oxygen reduction reaction (ORR) has attracted much attention. Herein, we fabricated iron phosphide/N, P-doped carbon nanosheets electrocatalysts via a one-pot pyrolysis process without any post-treatments, which shows high ORR activity over the whole pH range. In alkaline solution, the optimal catalyst exhibits almost the same onset potential (0.918 V vs RHE) and half-wave potential (0.832 V vs RHE) with commercial Pt/C (20 wt %), meanwhile it shows prominent catalytic activity compared with Pt/C in acidic and neutral media. Noteworthy, the catalyst catalyzes ORR process following a one-step 4e pathway in all these media and poses better tolerance toward methanol and greater durability than Pt/C. It was proved that Fe x P (x = 1 or 2) and N, P-doped carbon synergistically contributed to the high ORR activity for the electrocatalysts. This work would broaden the application of iron phosphides in the field of electrocatalysis.